2002
DOI: 10.1139/p02-059
|View full text |Cite
|
Sign up to set email alerts
|

Studies on muonic dynamics of liquid D–T–H in dtμ muonic-molecule resonance formation and its comparison with a D–T system

Abstract: Recent experimental and theoretical studies on muon-catalyzed fusion in a mixture of three gases, D-T-H, have shown that the muon-cycling-rate changes obtained are mostly in contradiction with each other and depend strongly on the physical conditions of the system. In this paper, we have considered the muon-cycling rate and its relevant nonlinear dynamical equations for mixtures of D-T and D-T-H in practical conditions where the muon-cycling rate is temperature; density of the mixture; and relative-particle co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Muonic helium atoms are the unusual pure atomic three body systems without any restriction due to Pauli exclusion principle for electron and muon being non-identical fermions. These are formed as by-products of the process of muon catalyzed fusion, hence are useful to understand the fusion reactions properly [4,5]. The electromagnetic interaction between the electron and negatively charged muon can be better understood by this simplest muonic system by precise measurements of hyperfine structure [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muonic helium atoms are the unusual pure atomic three body systems without any restriction due to Pauli exclusion principle for electron and muon being non-identical fermions. These are formed as by-products of the process of muon catalyzed fusion, hence are useful to understand the fusion reactions properly [4,5]. The electromagnetic interaction between the electron and negatively charged muon can be better understood by this simplest muonic system by precise measurements of hyperfine structure [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…These atoms/ions are generally formed as by-products of the process of muon catalyzed fusion, hence are useful to understand the fusion reactions in a proper way [4][5]. Although, hyperfine structure of these atoms are studied by several groups to interpret the nature of electromagnetic interaction between the electron and negatively charged muon [6][7], less attention have been given towards ab-initio calculation for the bound state observables of such exotic atoms/ions in the few-body model approach.…”
Section: Introductionmentioning
confidence: 99%
“…Several reasons have been stated in the literature regarding the importance of these exotic atoms: i) Muonic helium atoms are the unusual pure atomic three body systems without any restriction due to Pauli exclusion principle for electron and muon being non-identical fermions. ii) These are the by-products of the process of muon catalyzed fusion and study of these may yield useful information to understand the fusion reactions properly [5][6]. iii) The electromagnetic interaction between the electron and negatively charged muon can be better understood by this simplest muonic system by precise measurements of hyperfine structure [7][8] of the ground-state, in terms of interaction between the spin magnetic moments of muon and electron.…”
Section: Introductionmentioning
confidence: 99%
“…U nfortunately, attempts to produce commercial energy by muon-catalyzed fusion in muonized D Ϫ T molecule, the most promising candidate, were unsuccessful up to now. A candidate to explore high fusion rate is the doubly muonic molecule formation, where two muons are replaced with electrons in D 2 and D Ϫ T molecules, shown as dd and dt, respectively [1], but even if one were to find a way to produce these it will not gain more efficiency as the issue is one of molecular formation rates and muon sticking fractions, which completely determine the efficiency [2,3]. It is shown that the fusion rate of the deuterium-tritium muonic molecule, in which both electrons are replaced by the much heavier muons, are 40 times greater than that of the dt muonic molecule, in which only one of the electrons is replaced by muon [4].…”
Section: Introductionmentioning
confidence: 99%